Humidity Profiles Retrieved From GNSS Radio Occultations by a Non-negative Residual Constrained Least Square Error Method - Andrisaniand, Andrea; Vespe, Francesco (Frontiers in Earth Science, 2020)
We performed some refinements to the Boundary Profile eValuation (BPV) method, developed by Vespe and collaborators, for the retrieval of vertical atmospheric humidity profiles from Radio Occultation (RO) observations. Previous BPV models solve typical rank deficiencies in treating RO data by recurring to parametric dry atmospheric refractivity models, such as the Hopfield or the CIRA86aQ. The involved parameters were selected by fitting observed RO bending angles (BA) through the stratosphere where the humidity is negligible. Total refractivity was then obtained from observed bending angles via a variational method. Such approach furnishes a valid alternative to the usual Abel inversion. Humidity profiles were finally achieved by subtracting the dry refractivity contributions from the total refractivity profiles. Nevertheless, unphysical behaviors of “negative” values of humidity can occur when the dry refractivity profiles are extrapolated toward the lower part of the troposphere. In order to avoid such unphysical behavior, in this work we recur to a second fit for the total refractivity data, through a least square error method having a non-negative residual constrain. This is mathematically achieved with a modification of the usual least square error functional to minimize, by means of an additional exponential fast increasing term with respect to negative residuals. A Levenberg-Marquardt method relative to this new functional has been developed too, in order to numerically estimates the relative minimizers. With this approach new dry refractivity profiles, more suited to be extrapolated in the troposphere, are recovered. We tested this new method with a series of almost 450 of GPS-RO observations from the FORMOSAT-3 COSMIC-1 Space Mission in 2009. The results show that unphysical negative values for partial water vapor pressures are removed, without loosing, but in most cases even improving, the accuracy of the retrieved values, as compared with data from ECMWF and NCEP meteorological analysis, COSMIC data analysis as well, and RAOB balloons excursions suggests